Identifying patients for safe early hospital discharge following st elevation myocardial infarction. Issue 7 (29th November 2016) - Sharkawi, Musa A.; Filippaios, Andreas; Dani, Saurabh S.; Shah, Sachin P.; Riskalla, Nabila; Venesy, David M.; Labib, Sherif B.; Resnic, Frederic S.
Abstract : Objectives: To examine whether the CADILLAC risk score is an effective method of patient stratification for early discharge following ST elevation myocardial infarction (STEMI). Background: Patients with STEMI are typically hospitalized to monitor for serious complications such as arrhythmias, heart failure, and reinfarction. Optimal length of stay is unclear. Whether low risk patients can be safely discharged before 72 hr of hospitalization is unclear. Methods: Patients with STEMI who underwent successful PCI were retrospectively stratified using CADILLAC risk score to low risk ( n  = 123) and intermediate to high risk ( n  = 105). The primary outcome was adverse clinical events at day 3 or later. Secondary outcomes were adverse clinical events on day 1 and mortality rates at 30 days and 31 to 365 days. Results: Low risk patients had lower major adverse clinical events at day 3 or later (0 vs. 11.4%, P  = 0.0002) and lower total mortality at 1 year (0 vs. 4.8%, P  = 0.02) than patients with intermediate to high risk. Low risk patients were also less likely to have a cardiovascular event during the first 24 hr when compared to those with an intermediate to high risk score (3.3% vs. 13.3%, P  = 0.006). Conclusion: Low risk patients identified using CADILLAC risk score with STEMI treated successfully with primary PCI have a low adverse event rate on the third day or later of hospitalization suggesting that an earlier discharge is safe in properly selected patients. Monitoring in a noncritical care setting following primary PCI for STEMI may be feasible for selected patients. © 2016 Wiley Periodicals, Inc.